Psychological Profiles of Chinese Patients With Hemodialysis During the Panic of Coronavirus Disease 2019 - Yang, Zhen-Hua; Pan, Xiao-Ting; Chen, Yu; Wang, Lu; Chen, Qiu-Xin; Zhu, Yan; Zhu, Yu-Jia; Chen, Yong-Xi; Chen, Xiao-Nong (Frontiers in Psychiatry, 2021)
Background: Hemodialysis patients not only suffer from somatic disorders but are also at high risks of psychiatric problems. Early this year, the outbreak of coronavirus disease 2019 (COVID-19) has caused great panic and anxiety worldwide. The impact of this acute public health event on the psychological status of hemodialysis patients and its relationship with their quality of life have not been fully investigated. Methods: This study comprised two parts. The initial study enrolled maintenance hemodialysis patients treated in Ruijin Hospital for more than 3 months from March to May 2020 during the ongoing COVID-19 pandemic. Patients completed three questionnaires including the Impact of Events Scale–Revised (IES-R), General Health Questionnaire-28 (GHQ-28), and Kidney Disease Quality of Life (KDQOL) Short Form (SF). Follow-up study was performed from December 2020 to January 2021, when the pandemic of COVID-19 has been effectively contained in China. Only patients enrolled in the initial study were approached to participate in the follow-up study. Results: There were 273 maintenance dialysis patients enrolled in the initial study and 247 finished the follow-up study. For the initial study, the estimated prevalence of nonspecific psychiatric morbidity was 45.8% (125/273) by GHQ-28. By IES-R, 53/273 (19.4%) patients presented with total scores above 24 that reflected clinical concerns. We found a significant difference regarding KDQOL scores between patients with different stress response (IES-R) groups (p = 0.026). Our follow-up study showed that KDQOL and SF-36 scores were significantly improved in comparison with those in the initial study (p = 0.006 and p = 0.031, respectively). Though total scores of GHQ-28 and IES-R did not change significantly, some subscales improved with statistical significance. Furthermore, gender, education background, and duration of hemodialysis were three factors that may affect patients' mental health, quality of life, or health status while dialysis duration was the only variable that correlated with those parameters. However, these correlations were combined effects of the COVID-19 pandemic and the dialysis itself. Conclusions: We found a correlation between changes in the mental health status of dialysis patients and changes in their quality of life. These responses were also mediated by patients' psychosocial parameters. Our results urge the necessity of psychotherapeutic interventions for some patients during this event.